Calcitriol analog ZK191784 ameliorates acute and chronic dextran sodium sulfate-induced colitis by modulation of intestinal dendritic cell numbers and phenotype - Strauch, Ulrike G (World J Gastroenterol, 2007)
AIM: To investigate the effects of ZK1916784, a low calcemic analog of calcitriol on intestinal inflammation. METHODS: Acute and chronic colitis was induced by dextran sodium sulfate (DSS) according to standard procedures. Mice were treated intraperitoneally with ZK1916784 or placebo and colonic inflammation was evaluated. Cytokine production by mesenterial lymph node (MLN) cells was measured by ELISA. Immunohistochemistry was performed to detect intestinal dendritic cells (DCs) within the colonic tissue, and the effect of the calcitriol analog on DCs was investigated. RESULTS: Treatment with ZK191784 resulted in significant amelioration of disease with a reduced histological score in acute and chronic intestinal inflammation. In animals with acute DSS colitis, down-regulation of colonic inflammation was associated with a dramatic reduction in the secretion of the proinflammatory cytokine interferon (IFN)-γ and a significant increase in intereleukin (IL)-10 by MLN cells. Similarly, in chronic colitis, IL-10 expression in colonic tissue increased 1.4-fold when mice were treated with ZK191784, whereas expression of the Th1-specific transcription factor T-beta decreased by 81.6%. Lower numbers of infiltrating activated CD11c(+) DCs were found in the colon in ZK191784-treated mice with acute DSS colitis, and secretion of proinflammatory cytokines by primary mucosal DCs was inhibited in the presence of the calcitriol analog. CONCLUSION: The calcitriol analog ZK191784 demonstrated significant anti-inflammatory properties in experimental colitis that were at least partially mediated by the immunosuppressive effects of the derivate on mucosal DCs.